Hubungan Pengetahuan Ibu Tentang Isi Piringku Dan Pemberian Asi Eksklusif Dengan Status Gizi Balita Usia 1-5 Tahun - Ainun Mudholifah; I Dewa Nyoman Supariasa; Asworoningrum Yulindahwati; Reni Wahyu Triningsih (Journal of Innovative and Creativity, 2025)
Nutritional problems are closely related to the availability and accessibility of food in society. This low level threatens to reduce consumption of diverse and nutritionally balanced foods. This will have an impact on the high problem of malnutrition in society, especially in vulnerable groups such as mothers, babies and children. The aim of the research was to identify the relationship between mothers' knowledge about the contents of my plate and exclusive breastfeeding with the nutritional status of toddlers aged 1-5 years at Posyandu Petungsewu Barat, Petungsewu Wagir Village, Malang Regency. This type of quantitative research with an observational analytical research design was carried out in March 2024 at Posyandu Petungsewu Barat. Sampling was taken using purposive sampling technique. Data were analyzed using the Spearman Rank statistical test with a significance level of 0,05. The results of the Spearman Rank statistical test showed that the mother's knowledge about the contents of my plate had a p-value of 0,023 (≤0,05) and exclusive breastfeeding had a p-value of 0,009 (≤0,05). It can be concluded that there is a relationship between mother's knowledge about the contents of my plate and exclusive breastfeeding with the nutritional status of toddlers.